A prospective study of hearing impairment in school going children of Ghaziabad city attending a tertiary care hospital - Chishty, Saud Lateef; Hamid, Sajad; Lateef, Esbah-i; Chishty, Mohd Lateef; Wani, Asif; Najeeb, Qazi (International Journal of Research in Medical Sciences, 2017)
Background:Overcrowding, poor hygiene, socio-economic status, climate, lack of resources to avail medical facilities, poor medical awareness have their bearing on the incidence of hearing loss. The family of each hearing-impaired child has its own cultural, social, educational, and financial background, and its own special needs. The aim of this study is to determine the percentage of hearing impaired school going children in Ghaziabad city. Methods:The material for the present study were a representative sample constituting 1000 school children selected from various localities of Ghaziabad city within age group of 6-12 years. The children belonged to all the strata of society and children from both sexes were evaluated for hearing loss and its underlying etiological factors. Children were subjected to detailed ENT examination in our OPD. Results:In the present study sample the incidence of hearing loss is 9.3%. The maximum cases 60.22% belonged to the low socio-economic strata. A statistically significant difference of distribution by gender was noticed with a male preponderance (61.29%) as against 38.71% for females. The hearing loss in majority of cases was of a mild degree i.e., 26 to 45 dB (34.41%) of which majority of cases (87.10%) had conductive loss. Wax was the commonest cause of hearing loss (41.94%). CSOM was found in 21.50 % of all cases. Peak prevalence of hearing loss was found at 8 years of age, again declining after that from 20.43 % to 5.38 % by 12 years of age. Also it was observed that 59.14% children were living in crowded localities of city & 40.86% were living in non- crowded/open locality which is again statistically significant (P ≤0.05). Conclusion:The inferences drawn from the present study substantiates the view point of earlier workers that school screening is the most effective method of diagnosing deafness in school going children and should be extended to all schools in all the areas. Proper assessment and diagnosis of hearing loss in children at a very early age is important because an early diagnosis determines the efficacy of methods used for the correction of the hearing loss. Also early diagnosis of hearing impairment is a key to proper rehabilitation. The cases reporting to the hospital for treatment and rehabilitation can be regarded as the tip of the ice-berg and can have more management difficulties when compared to sub-clinical cases.